Internalisasi Nilai-Nilai Pendidikan Islam dalam Organisasi Pencak Silat Pagar Nusa - Wakib Kurniawan; Lilik Susanti; Zaidatul Inayah (Bustanul Ulum Journal of Islamic Education, 2024)
The approach to Islamic education through martial arts organizations, such as PSNU Pagar Nusa, holds significant potential in shaping the character of the youth based on Islamic values. However, limited research has delved into how this martial arts organization internalizes Islamic educational values in Lampung Province. This study aims to identify and analyze the Islamic educational values internalized through PSNU Pagar Nusa in Lampung Province and their implications for the behavior and character of the students. This research employs a qualitative approach with a descriptive-analytical method. Data were collected through in-depth interviews, observations, and documentation from PSNU Pagar Nusa members and relevant community figures. The findings reveal that Islamic values such as i’tiqadiyyah (faith), khuluqiyyah (ethics), and amaliyyah (practice) are successfully instilled through various activities such as martial arts training, Quranic recitation, and congregational prayers. These values manifest in the daily attitudes and behaviors of the students, reflecting discipline, responsibility, tolerance, and compassion towards all creatures. The implications of internalizing these values include the formation of resilient, virtuous, and positively influential youth within the community. The study concludes that PSNU Pagar Nusa not only plays a role in preserving traditional martial arts but also effectively shapes the Islamic character of its members.